CoFe2O4/rGO nanocomposite: Synthesis and enhanced ammonia gas sensing properties at room temperature - Marimuthu Ganesan; Bharathi Ganapathi; Palanisamy Govindasamy; Balaji Parasuraman; Paramasivam Shanmugam; Rajender Boddula; Ramyakrishna Pothu; Pazhanivel Thangavelu (Results in Chemistry, 2024)
In this study, CoFe2O4 and CoFe2O4/rGO samples were synthesized using co-precipitation and wet impregnation methods, respectively, and their sensing capabilities were assessed for ammonia gas detection at room temperature. The formation of the CoFe2O4/rGO nanocomposite was thoroughly examined through various analytical techniques, revealing its enhanced properties. Notably, the CoFe2O4/rGO nanocomposite exhibited significantly higher sensitivity compared to pure CoFe2O4, with a calculated sensitivity value of 1.098. The material also demonstrated rapid response and recovery times of 61 s and 143 s, respectively, for a 100-ppm ammonia gas concentration at room temperature. These findings highlight the potential of the CoFe2O4/rGO nanocomposite for efficient and sensitive gas sensing applications.